Experimental investigation on the cracking of pre-combustion cracking gas with gliding arc discharge plasma. (19th February 2021) - Kai, Zhang; Feilong, Song; Di, Jin; Shida, Xu; Jiulun, Sun; Shengfang, Huang
Abstract: To improve the quality of pre-combustion cracking gas, the gliding arc discharge plasma is adopted in this paper. The influence of incoming flow rate, electrode gap distance and discharge frequency on cracking effect have been experimentally studied. The results show that through plasma cracking, the concentration of H2 increases while the concentration of CH4 and C2 H4 decrease. With different fuel ratio conditions, the variation trend of C/H ratio as well as the mass flow of carbon and hydrogen atoms in the cracking products vary from each other. The cracking effect becomes weaker with the increase of incoming flow rate, while is better when the fuel ratio is larger. Given the flow rate of 18slpm and 24slpm, the best cracking effect can be acquired with the electrode gap of 1.5 mm. Besides, the effect of gliding arc discharge plasma cracking is weakened as the discharge frequency rises. Graphical abstract: Image 1 Highlights: Gliding arc discharge plasma is adopted to improve pre-combustion cracking. A combined cracking system is established and related experiments are carried out. The variation rule and reaction path of main components are researched. The cracking system is suitable for aircraft to improve fuel activity.